Analysis of the influence of part thickness on the replication of micro-structured surfaces by injection molding. (5th April 2016) - Masato, Davide; Sorgato, Marco; Lucchetta, Giovanni
Abstract: The achievement of an adequate accuracy of the microinjection molding process applied to the replication of micro-features is a complex task. The selection of process parameters and the geometry of the molded part influences the filling flow of the melt inside the mold cavity as well as the final quality of the replicated micro-features. In this work, the replication of a micro-structured surface is studied in relation to the thickness of the molded part. In particular, the effects of a rapid heat cycle molding process, cavity air evacuation, part thickness are experimentally evaluated. The analysis of the experimental data showed that the thickness of the main flow region and the molding temperature are significant factor affecting the replication quality. In particular, a combination of small cavity thickness and a high mold temperature (above T g ) can be effective in increasing the replicated height of micro-features. Experimental results also point out the correlation between the holding pressure and the distance from the injection location. An effective approach to the design of both the part and the process, should consider that the selection of process parameters must be related to design of the mold cavity. Graphical abstract: Highlights: Micro-injection molding of a micro-pillared surface for biomedical application Relation between cavity design and state-of-the-art micro-injection molding technologies A smaller cavity thickness increases the replicated height of micro-features. The application of vacuum venting has no significant effect on the replication. The holding pressure can be effectively exploited to improve the replication close to the injection location.